PELATIHAN KESIAPSIAGAAN MENGHADAPI BENCANA UNTUK ANAK USIA DINI - S. Damayanti; K.W. Purnawati; N.M.A. Dewi; N.P.L. Wedayanti; N.L.P.A. Sulatri; N.P.C. Lestari; I.G.G.P.A. Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Batubulan Village, Sukawati District, Gianyar Regency, is one of the areas in Bali that is prone to earthquake and tsunami disasters. This community service in the form of disaster preparedness training given to teachers and children of Bali Kumara Kindergarten aims to increase knowledge and skills in dealing with natural disasters, especially earthquakes and tsunamis. This training combined three disaster education methods, which included the kamishibai method or storytelling